A practical investigation of wideband impedance based fault location technologies - Jahanger, Hayder Kadhim Jahanger (2019)
This thesis presents a thorough investigation of newly developed impedance-based estimation techniques that use the fault generated transient in order to locate faults in Integrated Power Systems (IPS) or Microgrids such as those existing in modern ships and aircraft. The methods studied use the high frequencies generated by the fault.